First Record of Pyramica epinotalis (Hymenoptera: Formicidae) for the United States - Xuan Chen; Joe A. MacGown; Benjamin J. Adams; Katherine A. Parys; Rachel M. Strecker; Linda Hooper-Bui (Psyche: A Journal of Entomology)
Pyramica epinotalis is an arboreal dacetine ant previously known only from Brazil, Costa Rica, Ecuador, and southern Mexico. Here we report the first records of P. epinotalis for the United States. Collections were made in three parishes across southern Louisiana in cypress-tupelo swamps using floating pitfall traps placed in floating vegetation and arboreal pitfall traps placed on trunks and limbs of three wetland tree species. One additional specimen of this species was collected in Highlands County, Florida. Based on collections of specimens in Louisiana, including multiple dealate females at different localities, P. epinotalis appears to be well established in this state. We discuss the design and implementation of modified arboreal pitfall traps that were instrumental in this discovery.